(untitled) - Lewis, Marilyn (New York, 2003)
Students who speak English as a second language and who are studying in a new country are taking a big step. How do they choose subjects? Can they go and talk with the lecturers? What about making friends? In this book students will find practical answers to these and other frequently asked questions, written in straightforward English.
Keywords: English language,English language; Spoken english,Problems, exercises, etc,Textbooks for foreign speakers